(untitled) (Third Sector Social Economic Review, 2013)
One of the most important problems of developing countries is insufficient capital accumulation, to reduce this deficit, one of the alternative approaches that is offered is increasing the amount of foreign direct investments (FDI). Foreign direct investment manipulates numerous economic indicators pertaining to host nation such as employment, economic boost, balance of payment, export, inflation.The structural problems, risk and uncertainties, and integration issues of agriculture sector with world economics as well as the rapid growth rate among the major reasons of low direct foreign investment realized in agriculture sector.In terms of more balanced development among the economic sectors and employment of rural labor, the proportion of direct foreign investment of agriculture sector should be increased. For this reason, special attention should be given to the solutions of structural problems of agriculture sector and the required legal and financial arrangements should be made.